Tsetse control: progress report - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The fight against the tsetse fly (Glossina spp.) which spreads trypanosomes that cause sleeping sickness is still being fought, with insecticides. But the pyrethrum-based insecticides in use today are less powerful than the more...